Redefining the Role of NATO in MENA Region in the Aftermath of the Cold War: future prospects as a global security enabler and partner - Abu Anzeh, Mohammad (Dirasat: Human and Social Sciences, 2021)
Since the end of the Cold War, the North Atlantic Treaty Organisation (NATO) has been undergoing an evolutionary process of redefining its mandate and posture in order to remain relevant as a security provider. This evolutionary process has centered on NATO’s expansion from a static defense alliance into an organisation with a regional and global outlook on security challenges, reflecting the view that the security of the Alliance’s members is now threatened by issues emanating from regions far flung from mainland Europe. Accordingly, the Middle East and North Africa (MENA) region has emerged as a key regional focus of NATO’s expanding focus. However, this expanding focus is facing numerous challenges, ranging from internal NATO divisions to historical and cultural barriers hampering the establishment of a genuine cooperative security community between NATO and its MENA partners. As such, this paper seeks to tackle the question of is NATO’s evolving role and engagement in MENA enabling it to contribute to the future peace and security of the region? To tackle this question, section 1 will provide the historical context that has been the foundation for NATO’s push into MENA, namely the Alliance’s efforts to redefine itself as a global security provider. Section 2 surveys how this push has played out so far, outlining how the broader forces defining much of NATO’s wider global engagement – the increasing prevalence of inter-alliance divisions and NATO’s strategy of pursuing partnership initiatives – have likewise played out in the Alliance’s MENA presence.